Fuzhuan brick tea polysaccharides serve as a promising candidate for remodeling the gut microbiota from colitis subjects in vitro: Fermentation characteristic and anti-inflammatory activity - Chen, Guijie; Wang, Mingjia; Zeng, Ziqi; Xie, Minhao; Xu, Weiqi; Peng, Yujia; Zhou, Wangting; Sun, Yi; Zeng, Xiaoxiong; Liu, Zhonghua (Food chemistry, 2022)
•FBTPS-3 could be utilized and degraded by inflammatory bowel disease (IBD) gut microbiota.•FBTPS-3 modulated the composition and structure of IBD gut microbiota.•FBTPS-3 could reverse Bacteroides and Escherichia/Shigella in IBD gut microbiota.•The metabolites of FBTPS-3 by gut microbiota showed significantly anti-inflammatory activity.•FBTPS-3 was expected as novel prebiotics for treatment of IBD. The purified fraction 3 of polysaccharides from Fuzhuan brick tea (FBTPS-3) could attenuate the colitis and modulate the gut microbiota. However, the relationship between anti-inflammatory effect of FBTPS-3 and the gut microbiota is still unknown. Thus, the anaerobic fermentation in vitro was used to investigate the potential mechanism. FBTPS-3 could be utilized and degraded by gut microbiota from inflammatory bowel disease (IBD) subjects. Furthermore, FBTPS-3 could modulate the composition and structure of IBD gut microbiota toward to that of healthy group. FBTPS-3 showed a superior modulated effect on IBD gut microbiota by increasing Bacteroides and decreasing Escherichia/Shigella. Furthermore, the fermentation solution rather than FBTPS-3 itself showed anti-inflammatory effects on lipopolysaccharide-treated RAW264.7 macrophages, which might be due to the metabolites such as short-chain fatty acids (SCFAs). Thus, FBTPS-3 can be expected as novel prebiotics for treatment of IBD via modulating gut microbiota, and promoting the production of SCFAs.